Editor’s Introduction: Amor Narratio - Tamboukou, Maria (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2020)
In this paper, the editor of this special issue introduces Catherine Kohler Riessman’s festschrift by making connections between its title, amor narratio and the notion of amor mundi in Hannah Arendt’s philosophical thought. The author asks what it is about Riessman’s scholarship that has inspired love for narratives. In doing so she looks at the contradictions in Arendt’s take on love, highlighting understanding and critical thinking as its most salient features, but also as the two main strands that correspond to the notion of amor narratio in Riessman’s narrative scholarship. Amor narratio eventually becomes the red thread that brings together the contributions of this volume in different manifestations and expressions.